PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA BOX TO THE WORLD OF INTELLIGENCE TERHADAP KETERAMPILAN MENULIS SISWA SD - Latifatul Mutoharoh, Dhenok; Hawa, Anni Malihatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is the low level of writing skills among third-grade elementary school students. This study aims to determine the differences in and the influence of the Discovery Learning model supported by "Box to the World of Intelligence" media on students' writing skills. A quantitative approach was employed using a quasi-experimental design, specifically the Nonequivalent Control Group Design. The sample was selected via purposive sampling and consisted of 35 students: 20 in the experimental class and 15 in the control class. Data collection involved test techniques, non-test techniques, and documentation. The results revealed a significant difference in writing skills between the experimental and control classes; the Independent Samples t-test yielded a significance value of 0.001 (p < 0.05), leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). Furthermore, a simple linear regression analysis showed a significance value of 0.004 (p < 0.05), also resulting in the rejection of H0 and the acceptance of Ha. Thus, it can be concluded that the Discovery Learning model, supported by "Box to the World of Intelligence" media, has a significant influence on the writing skills of third-grade elementary school students.